2016
DOI: 10.1371/journal.pone.0159999
|View full text |Cite
|
Sign up to set email alerts
|

BipA Is Associated with Preventing Autoagglutination and Promoting Biofilm Formation in Bordetella holmesii

Abstract: Bordetella holmesii causes both invasive and respiratory diseases in humans. Although the number of cases of pertussis-like respiratory illnesses due to B. holmesii infection has increased in the last decade worldwide, little is known about the virulence factors of the organism. Here, we analyzed a B. holmesii isolate that forms large aggregates and precipitates in suspension, and subsequently demonstrated that the autoagglutinating isolate is deficient in Bordetella intermediate protein A (BipA) and that this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
4
11
0
Order By: Relevance
“…Since BipA is highly conserved amongst bacteria 36,37,49 it is tempting to speculate that the BipA-dependent control of biofilm formation by temperature observed in V. cholerae could be conserved in other bacteria. In agreement with this hypothesis, deletion of BipA has been associated to increased biofilm levels in P. aeruginosa PAO1 41 and Bordetella holmesii 45 . BipA from E. coli and P. aeruginosa cross-complemented V. cholerae ΔbipA temperature-dependent phenotypes (Figure 3D), further supporting a model of BipA function as a bacterial “temperature sensor”.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Since BipA is highly conserved amongst bacteria 36,37,49 it is tempting to speculate that the BipA-dependent control of biofilm formation by temperature observed in V. cholerae could be conserved in other bacteria. In agreement with this hypothesis, deletion of BipA has been associated to increased biofilm levels in P. aeruginosa PAO1 41 and Bordetella holmesii 45 . BipA from E. coli and P. aeruginosa cross-complemented V. cholerae ΔbipA temperature-dependent phenotypes (Figure 3D), further supporting a model of BipA function as a bacterial “temperature sensor”.…”
Section: Discussionsupporting
confidence: 70%
“…Mutations in BipA have been associated with a cold-sensitive phenotype in E. coli 44 , but a clean deletion of vc2744 in V. cholerae co969 did not influence growth or cell morphology at any temperature (SM Figure 3). In other bacteria, BipA has been implicated in biofilm formation 41,45,38,46 , but the mechanism behind this phenotype has remained elusive. As BipA is thought to be a ribosome-binding GTPase that regulates ribosome assembly 47 , we reasoned that VC2744 could be repressing biofilm development at low temperatures through translational regulation.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we used a mouse intranasal challenge model, as the model is strongly correlated with the efficacy of vaccines in humans and is, so far, the sole model system that is used for in vivo studies of B. holmesii . In fact, studies of Zhang et al and the present study clearly suggested that commercial pertussis vaccines had little effect against B. holmesii .…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, BipA is not strictly required for colonization of the respiratory tract by B. pertussis but is, instead, necessary immediately before and/or after a transmission event . However, the initial level of colonization by B. holmesii strain BH2Sm r ‐ΔBipA was found to be significantly lower than that of the wild‐type strain in a murine model . Thus, the BipA‐like protein of B. holmesii might be involved in binding to the respiratory tract and might play an important role in protection of mice that have been immunized with aBH vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation